Conversion of cassava rhizome to alternative biofuels via catalytic hydrothermal liquefaction - Parinvadee Chukaew (2022)
In this study, cassava rhizome was converted to alternative biofuels including biocrude oil (BO) and hydrochar (HC) using catalytic hydrothermal liquefaction (C-HTL) at 250 and 300℃ for 15 min using 4.0 wt.% of K2CO3 as a catalyst. BO and HC properties were investigated regarding the parameters of elemental composition, chemical functional groups, chemical compositions, and surface morphology. The maximum energy recovery efficiency (ERE) of sum product (83.98 wt.%) was derived at 300℃. Therefore, 300℃ was suggested as a promising C-HTL temperature. This condition derived a yield of BO and HC at 33.70 and 33.29 wt.%, with their Higher heating value (HHV) at 26.45 and 18.81 MJ/kg, respectively. Gas chromatography-mass spectroscopy (GC-MS) analysis results indicated that BO principally contains phenols, aldehydes and ketones, hydrocarbons and alcohols which can be fractionated and upgraded into the biofuels and various valuable chemicals. The hydrogen/carbon (H/C) and oxygen/carbon (O/C) atomic ratios of BO and HC were similar to those of fossil fuel, indicating their high potential as fossil fuel substituting materials.